Critical Study of Bank Interest Using Double Movement Hermeneutics from the Perspective of Fazlur Rahman - Nihayah, Ana Zahrotun; Musahadi; Muhlis; Rifqi, Lathif Hanafir (LPPM, Universitas Islam Syarifuddin Lumajang, 2025)
This study discusses the practice of bank interest using the double movement hermeneutic approach developed by Fazlur Rahman. This approach consists of two main stages: first, reconstructing the social and historical context in which the verses on usury were revealed to understand the moral and sociological background of the prohibition; second, updating the universal moral values contained in the verses to make them relevant to modern life and economic system. This study uses a qualitative method with an in-depth literature study approach to the works of Fazlur Rahman, academic literature, and verses of the Qur'an related to usury. The results of the study show that bank interest cannot be classified as usury unless it contains elements of injustice and exploitation. In a modern profit-oriented financial system, interest is seen as a form of compensation for the risk and service of using funds. This insight has global relevance as the contemporary Islamic financial system continues to face challenges in bridging Shari'ah principles with the realities of the modern economy.